ONLY: An NPI-licenser and NPI-unlicenser. (17th May 2017) - Xiang, Yimei
Abstract: It is commonly argued that weak negative polarity items (NPIs) (e.g. any ) can occur in any (Strawson) downward-entailing environment. This generalization, however, is challenged by Wagner's (2006) observations with the NPI-licenser only : although an only -clause is (Strawson) downward-entailing in its unfocused part, NPIs are not necessarily licensed there. In particular, DP- only does not license an NPI that appears within the unfocused part of its left argument (as seen in *Only a chair of any HUMANITIES F department met with the president ), and VP- only does not license an NPI if this NPI and the focused item appear within the same island (as seen in *The president only met with a chair of any HUMANITIES F department ). These observations suggest that the licensing status of an NPI in an only -sentence is not just determined by the polarity pattern of the environment where this NPI gets interpreted. To explain Wagner's (2006) observations, I argue that only is not just an NPI-licenser but also an 'NPI-unlicenser.' Following Chierchia (2006, 2013), I assume that an NPI carries a domain feature [D] which activates domain alternatives, and that an NPI is unlicensed if exhaustifying its domain alternatives yields a contradiction. I further propose that only can check off the [D] feature of an NPI that appears within its syntactic argument. If the argument of only is downward-entailing with respect to an NPI, using only to check off the [D] feature of this NPI would return an inference that contradicts the prejacent presupposition and make this NPI unlicensed. In the case of VP- only association, if an NPI is not focused and doesn't appear within a focus-contained island, the contradiction can be avoided by F-movement.